Finite element modeling and experimental studies on mixed mode-I/III fracture specimens - M. Bozkurt; A. O. Ayhan; M. F. Yaren; S. İriç (Fracture and Structural Integrity)
In this study, finite element modeling and experimental studies on a mode-I/III specimen similar to the compact tension specimen are presented. By using bolts, the specimen is attached to two loading apparatus that allow different levels of mode-I/III loading by changing the loading holes. Specimens having two different thicknesses are analyzed and tested. Modeling, meshing and the solution of the problem involving the whole assembly, i.e., loading devices, bolts and the specimen, with contact mechanics are performed using ANSYSTM. Then, the mode-I/III specimen is analyzed separately using a submodeling approach, in which threedimensional enriched finite elements are used in FRAC3D solver to calculate the resulting stress intensity factors along the crack front. In all of the analyses, it is clearly shown that although the loading is in the mode-I and III directions, mode-II stress intensity factors coupled with mode-III are also generated due to rotational relative deformations of crack surfaces. The results show that the mode-II stress intensity factors change sign along the crack front and their magnitudes are close to the mode-III stress intensity factors. It is also seen that magnitudes of the mode-III stress intensity factors do not vary much along the crack front. Fracture experiments also performed and, using the stress intensity factors from the analyses and crack paths and surfaces are shown.